Can geoengineering be optimised? - Hornigold, T (2023)
Geoengineering is the intentional, large-scale manipulation of Earth’s climate. It has been suggested that this could be done to counteract or ameliorate the effects of anthropogenic climate change, to reduce its negative impacts or buy time for global greenhouse gas emissions to be reduced. Stratospheric aerosol injection, where aerosols in the stratosphere are used to reflect sunlight and so cool climate, has been widely studied. Altering the altitude, latitude, or timing of aerosol injections could result in different radiative forcing patterns, which suggests there may be potential to “optimise” stratospheric aerosol injection geoengineering to achieve particular climate goals. The extent to which geoengineering could be optimised, beyond idealised studies that counteract the global mean temperature increase of greenhouse gases, has only relatively recently begun to be explored.